Once upon a crime - Buckley, Michael, 1969- (Buckley, Michael, 1969- Sisters Grimm, 2017)
When the fairy-tale detectives rush to New York City hoping to find an Everafter who can cure Puck, they trigger a chain of events that includes a murder mystery, and learn many new things about their mother who, along with their father, is still in an enchanted sleep.